Phenomenological understandings of higher education students with flow in the online learning environment - Kumasaka, Katherine (Curtin University, 2024)
The growth of online courses in higher education is accompanied by issues concerning students’ motivation and engagement. Applying flow theory in a hermeneutic phenomenological approach assists in understanding how to enhance online learning environments and improve student experience. Data was collected through questionnaires, interviews and journaling. Conclusions revealed that flow is influenced by authentic real-world tasks, and self-efficacy. The study encouraged a richer understanding of flow and its meaning in the context of online learning.